(3EfLGR GdeYQha hYeOI Gdedghas - (3YHO Gdedc Hf eMeO Hf ESeGYjd, CHh efUhQ GdKYGdHj,J (B429 (3g` s
(3ChdgG (B:s
(3GdMeO ddg LGeY GdTJGJ, heNQL GdfHGJ, heMjj GdQaGJ, hUdi Gddg Ydi SjOfG NGJe GdfHhGJ, heHdZ GdQSGdGJ s
(3BNQgG (B:s
(3fSCd Gddg Cf jLYdfG eef hSYJg QMeJg aTedg HGdYah hGdQVG hLYd GdLfI dg GdeChi eY fHjg GdeUWai hBdg GdWGgQjf GdCUajGA UdhGJ Gddg hSdGe Gddg Ydjg hYdjge CLeYjf Bejf s
(3Vef eLehY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B163s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs